Зміцнення деталей за допомогою поверхнево-пластичної деформації - Паніна, Валерія Валеріївна; Панина, Валерия Валерьевна; Panina, Valeriia; Дідур, В. В.; Сєрий, Ігор Сергійович; Серый, Игорь Сергеевич; Sieryi, Ihor; Чорна, Тетяна Сергіївна; Черная, Татьяна Сергеевна; Chorna, Tetiana (ТДАТУ, 2020)
UK: В статті розглядаються існуючі технології зміцнення поверхневого шару деталей з застосуванням поверхнево-пластичної деформації: дробоструминний наклеп; чеканка; гідроабразивний наклеп; безабразивна ультразвукова фінішна обробка; обкатка роликами або кульками. Розглянуті в статті методи поверхневої пластичної деформації забезпечують підвищення зносостійкості, опір втомі, контактної витримки та інших експлуатаційних властивостей деталей що оброблюються на 20-50%, а в деяких випадках – в 2-3 рази (при умові вибору в кожному конкретному випадку найбільш раціонального методу і призначенні оптимальних режимів обробки). Збільшення твердості і міцності металу поверхневим наклепом, а також ріст опорної поверхні при обкатуванні роликами дозволяють розглядати його як один з ефективних способів підвищення працездатності і, зокрема, зносостійкості деталей машин. RU: В статье рассматриваются существующие технологии упрочнения поверхностного слоя деталей с применением поверхностно-пластической деформации: дробеструйный наклеп; чеканка; гидроабразивный наклеп; безабразивная ультрозвуковая финишная обработка; обкатка роликами или шариками. Рассмотренные в статье методы поверхностной пластической деформации обеспечивают повышение износостойкости, сопротивление усталости, контактной выдержке и других эксплуатационных свойств, обрабатываемых деталей на 20-50%, а в некоторых случаях – в 2-3 раза (при условии выбора в каждом конкретном случае наиболее рационального метода и назначения оптимальных режимов обработки). Увеличение твердости и прочности металла поверхностным наклепом, а также рост опорной поверхности при обкатке роликами позволяют рассматривать его как один из эффективных способов повышения работоспособности и, в частности, износостойкости деталей машин. EN: Тhe article considers the existing technologies for strengthening the surface layer of parts using surface-plastic deformation: shotgun slander, which is carried out by a jet of steel or cast iron shot; processing is carried out by special fights which inflict numerous blows; defamation by rotational hardening, which causes numerous ordered blows by balls or rollers located on the periphery of rotating disks; hydroabrasive slander is carried out by a stream of liquid, which has abrasives of various granules; non-abrasive ultrasonic finishing allows you to turn machines into multi-operational, and significantly reduce surface roughness; treatment with rollers or balls reduces the tendency to the formation of burrs due to the greater oil content of the surface. Studies show that most methods of surface-plastic deformation not only reduce the roughness parameter by 5-10 times, but also create a favorable for wear resistance form of micro-irregularities, which is closer than with other methods of finishing, to the form of micro-irregularities created after running-in. The methods of surface plastic deformation considered in the article provide increase of wear resistance, fatigue resistance, contact exposure and other performance properties of parts processed by 20-50%, and in some cases – 2-3 times (provided thechoice in each case by the nearest rational method and certain optimal modes of blocks). Along with ensuring high surface quality, surface-plastic deformation in many cases allows mechanizing manual labor and increase productivity in the final operations. Increasing the hardness and strength of the metal by surface hardening, as well as the growth of the bearing surface when running in rollers allow us to consider it as one of the effective ways to improve performance and, in particular, wear resistance of machine parts
Упрочнение деталей с помощью поверхностно-пластической деформации
Strengthening of details by surface-plastic deformation
Keywords: поверхневий шар; метод зміцнення; поверхнево-пластична деформація; мікронерівності; підвищення працездатності; поверхностный слой; упрочнение; поверхностно-пластическая деформация; микронеровности; повышение работоспособности; surface layer; strengthening method; surface-plastic deformation; micro-inequalities; increase efficiency